Wnt/β-catenin signaling contributes to articular cartilage homeostasis through lubricin induction in the superficial zone - Xuan, Fengjun (Arthritis Res Ther, 2019)
BACKGROUND: Both loss- and gain-of-function of Wnt/β-catenin signaling in chondrocytes result in exacerbation of osteoarthritis (OA). Here, we examined the activity and roles of Wnt/β-catenin signaling in the superficial zone (SFZ) of articular cartilage. METHODS: Wnt/β-catenin signaling activity was analyzed using TOPGAL mice. We generated Prg4-Cre(ERT2);Ctnnb1(fl/fl) and Prg4-Cre(ERT2);Ctnnb1-ex3(fl/wt) mice for loss- and gain-of-function, respectively, of Wnt/β-catenin signaling in the SFZ. Regulation of Prg4 expression by Wnt/β-catenin signaling was examined in vitro, as were upstream and downstream factors of Wnt/β-catenin signaling in SFZ cells. RESULTS: Wnt/β-catenin signaling activity, as determined by the TOPGAL reporter, was high specifically in the SFZ of mouse adult articular cartilage, where Prg4 is abundantly expressed. In SFZ-specific β-catenin-knockout mice, OA development was significantly accelerated, which was accompanied by decreased Prg4 expression and SFZ destruction. In contrast, Prg4 expression was enhanced and cartilage degeneration was suppressed in SFZ-specific β-catenin-stabilized mice. In primary SFZ cells, Prg4 expression was downregulated by β-catenin knockout, while it was upregulated by β-catenin stabilization by exon 3 deletion or treatment with CHIR99021. Among Wnt ligands, Wnt5a, Wnt5b, and Wnt9a were highly expressed in SFZ cells, and recombinant human WNT5A and WNT5B stimulated Prg4 expression. Mechanical loading upregulated expression of these ligands and further promoted Prg4 transcription. Moreover, mechanical loading and Wnt/β-catenin signaling activation increased mRNA levels of Creb1, a potent transcription factor for Prg4. CONCLUSIONS: We demonstrated that Wnt/β-catenin signaling regulates Prg4 expression in the SFZ of mouse adult articular cartilage, which plays essential roles in the homeostasis of articular cartilage.